Autoimmunity Following Allogeneic Hematopoietic Stem Cell Transplantation - Buxbaum, Nataliya Prokopenko; Pavletic, Steven Z. (Frontiers in Immunology, 2020)
Autoimmune manifestations after allogeneic hematopoietic stem cell transplantation (AHSCT) are rare and poorly understood due to the complex interplay between the reconstituting immune system and transplant-associated factors. While autoimmune manifestations following AHSCT have been observed in children with graft-versus-host disease (GvHD), an alloimmune process, they are distinct from the latter in that they are generally restricted to the hematopoietic compartment, i.e., autoimmune hemolytic anemia, thrombocytopenia, and/or neutropenia. Autoimmune cytopenias in the setting of ASHCT represent a donor against donor immune reaction. Non-hematologic autoimmune conditions in the post-AHSCT setting have been described and do not currently fall under the GvHD diagnostic criteria, but could represent alloimmunity since they arise from the donor immune attack on the antigens that are shared by the donor and host in the thyroid, peripheral and central nervous systems, integument, liver, and kidney. As in the non-transplant setting, autoimmune conditions are primarily antibody mediated. In this article we review the incidence, risk factors, potential pathophysiology, treatment, and prognosis of hematologic and non-hematologic autoimmune manifestations in children after AHSCT.